A particulate (ZnSe)0.85(CuIn0.7Ga0.3Se2)0.15 photocathode modified with CdS and ZnS for sunlight-driven overall water splitting. Issue 40 (28th September 2017) - Goto, Yosuke; Minegishi, Tsutomu; Kageshima, Yosuke; Higashi, Tomohiro; Kaneko, Hiroyuki; Kuang, Yongbo; Nakabayashi, Mamiko; Shibata, Naoya; Ishihara, Hitoshi; Hayashi, Toshio; Kudo, Akihiko; Yamada, Taro; et al.
Abstract : A photocathode prepared using the photocatalyst (ZnSe)0.85 (CuIn0.7 Ga0.3 Se2 )0.15 and modified with CdS/ZnS overlayers and a Pt catalyst, exhibits a photocurrent of 4.3 mA cm −2 at 0 VRHE under AM 1.5G simulated sunlight. Abstract : A photocathode prepared using the photocatalyst (ZnSe)0.85 (CuIn0.7 Ga0.3 Se2 )0.15 in powder form, and modified with CdS/ZnS overlayers and a Pt catalyst, exhibits a photocurrent of 4.3 mA cm −2 at 0 VRHE under AM 1.5G simulated sunlight. The photocathode was capable of utilizing photons up to 900 nm, while the onset potential was evaluated to be as high as 0.8 VRHE . Modification with thin CdS and ZnS layers significantly increases the cathodic photocurrent through the formation of a surface p–n junction. The half-cell solar-to-hydrogen conversion efficiency of 0.83% at 0.33 VRHE obtained from this device is among the highest yet reported for a photocathode fabricated from a particulate photocatalyst. A solar to hydrogen conversion efficiency of 0.60% was observed during bias-free overall water splitting using this photocathode together with a BiVO4 photoanode. The present work clearly demonstrates the possibility of efficient hydrogen generation using durable particulate semiconductor photoelectrodes.